Fracture mechanics analysis methods - Ng, Chun Da (Nanyang Technological University, 2020)
In this study, fracture mechanic analysis method was reviewed for the program development of the automated calculation of fatigue life cycles prediction. An integral expression was first developed from Paris’ law fatigue crack growth equation, followed by setting up an integration function in Excel spreadsheet using trapezoidal rule and Excel VBA to integrate the expression to determine the predicted fatigue lifespan (cycles). A UserForm was designed to facilitate data inputs and outputs display with a graphical plot of crack length vs fatigue life cycles. Influence of material constants C & m for two rail steel grades (R260, R350HT) at the head, web and foot were investigated and compared to establish critical values for both steel grades. The Stress Intensity Factor (SIFs) expressed in term of geometric Y factor developed by Y. Liu was used to investigate the effects of different crack angle, crack initiation location and loading type, each producing a specific trend in fatigue life cycles for the respective variable. The effect of critical stress on resulting fatigue life cycles was also studied and the results are characterised by a reverse exponential trend in fatigue lifespan with increasing stress value. Parametric studies were conducted extensively to ensure consistency in the results. The graphical plot of crack length vs fatigue life cycles provides an insight on crack growth trend which shows exponential crack propagation at a faster rate when the crack length grows beyond 1mm.